Household division of labor, partnerships and children: evidence from Europe - José Ignacio Giménez; José Alberto Molina; Almudena Sevilla Sanz (Institute for the Study of Labor (IZA), 2007)
This paper complements conventional economic analysis and presents a social norms interpretation to explain cross-country differences in partnership formation rates, and the dramatic decrease in partnership formation rates in Southern Europe in particular. We argue that increases in female human capital - by raising the opportunity cost of entering a partnership - had a differential impact on partnership formation rates in Northern and Southern Europe due to the different social norms regarding the household division of labor. Social norms are modeled as a constraint on the allocation of household labor that (if binding) diminishes the gains to enter a partnership. Furthermore, highly educated women are less likely to form a partnership, because the utility loss when a partnership is formed is lower the higher the female opportunity cost. We test the predictions of the model using 7 waves of the European Community Household Panel (1995-2001). For each country and year we construct the average of the female to male ratio of childcare time as an indicator of social norms regarding the household division of labor. The empirical findings support the predictions of the model. After controlling for the time and country variation in the data, as well as for permanent individual heterogeneity and other aggregate variables at the country level, the results suggest that more traditional social norms regarding the household division of labor negatively affect a woman's probability of forming a partnership. Thus, a woman living in a country with a more traditional division of household labor has, ceteris paribus, a lower probability of forming a partnership. Furthermore, as predicted by the theory, social norms have a stronger negative effect for highly educated women. To the extent that female education has increased over the years, and that Southern European countries have more traditional social norms, this latter finding may partly explain the dramatic decrease in partnership formation rates in Southern Europe.
Keywords: 330; Haushaltsproduktion; Ehe; Soziale Rolle; Geschlecht; Schätzung; Europa